The delivery of Ask-Advise-Connect for smoking cessation in Dutch general practice during the COVID-19 pandemic: results of a pre-post implementation study - Naomi A. van Westen-Lagerweij; Marc C. Willemsen; Esther A. Croes; Niels H. Chavannes; Eline Meijer (BMC, 2023)
Abstract Background The Ask-Advise-Connect approach can help primary care providers to increase the number of smokers that attempt to quit smoking and enrol into cessation counselling. The approach has not yet been implemented in general practice in the Netherlands. The aim of this study was to investigate the influence of a comprehensive implementation strategy on the delivery of Ask-Advise-Connect for smoking cessation within Dutch general practice during the COVID-19 pandemic. Methods A pre-post study was conducted between late 2020 and early 2022, and included 106 Dutch primary care providers (GPs, practice nurses and doctor's assistants). Participation lasted nine months: during the first three months participants delivered smoking cessation care as usual (pre-intervention); the implementation strategy came into effect after three months and participants were followed up for another six months (post-intervention). The implementation strategy consisted of two meetings in which participants were educated about Ask-Advise-Connect, made agreements on the implementation of Ask-Advise-Connect and reflected on these agreements. Participants also received online educational materials and a desk card as reminder. The changes in the proportions of 'Ask' and 'Advise' over time were modelled using linear mixed effects models. A descriptive analysis was conducted with regard to referrals to cessation counselling. Results Participants provided consultations to 29,112 patients (both smokers and non-smokers). Results of the linear mixed effects model show that the proportion of patients that were asked about smoking ('Ask') significantly decreased in the first three months (pre-intervention), but slightly increased again after the implementation strategy came into effect (post-intervention). No significant change over time was found with regard to the proportion of patients advised to quit smoking ('Advise'). Descriptive statistics suggested that more participants proactively (vs. passively) referred patients to cessation counselling post-intervention ('Connect'). Conclusions The findings indicate that a comprehensive implementation strategy can support primary care providers in offering smoking cessation care to patients, even under stressful COVID-19 conditions. Additional implementation efforts are needed to increase the proportion of patients that receive a quit advice and proactive referral.